Penyuluhan Pola Hidup Bersih Sehat (PHBS) Di SDN 01 Cimanggis Bojonggede Kabupaten Bogor - Emilda, Emilda; Hidayah, Muslihatul (Universitas Teuku Umar, 2020)
PHBS in schools is an important activity in order to prepare young people to be aware of health. Because the habits that are built from an early age will shape a person's behavior patterns in his adult life. The targets of this activity are students and teachers. This activity is carried out by empowering students and teachers to adopt healthy lifestyles to create healthy students and a clean school environment. The results of the activities showed that teachers and students already had general knowledge about. While the indicator for each PHBS point is not yet understood. Counseling activities are very minimal carried out both by schools and related agencies. Whereas the formation of PHBS characters requires repeated socialization and counseling. Counseling is more effective by using games, video and live demonstrations. Teachers and students are more enthusiastic about listening than just lecturing. More than that, schools need to complete supporting facilities and infrastructures to facilitate the implementation of PHBS in schools. And to realize it requires the contribution of other stakeholders, especially the government.Â